2010
DOI: 10.1093/qjmed/hcq113
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence after acute Q fever of non-infective Coxiella burnetii cell components, including antigens

Abstract: The study identifies a non-infective complex of C.b. antigens able to survive in the host and provoke aberrant humoral and cell medicated immunity responses - a possible pathogenic link between initial infection and a subsequent long-term post Q fever fatigue syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…94 NAAT-based testing of surgical materials may also detect organisms associated with previous episodes of IE that were treated up to 12 years before surgery and are unrelated to the current episode. 95,96 There is little loss of sensitivity by NAAT when surgical specimens are obtained within 5 days of initiation of antibiotic therapy; treatment for several weeks before surgery will increase the false-negative rate. 93,97 Investigational approaches to the pathogenesis of CNE include tissue-culture based growth for propagation of intracellular pathogens and autoimmunohistochemistry on surgical specimens.…”
Section: Culture-negative Endocarditismentioning
confidence: 99%
“…94 NAAT-based testing of surgical materials may also detect organisms associated with previous episodes of IE that were treated up to 12 years before surgery and are unrelated to the current episode. 95,96 There is little loss of sensitivity by NAAT when surgical specimens are obtained within 5 days of initiation of antibiotic therapy; treatment for several weeks before surgery will increase the false-negative rate. 93,97 Investigational approaches to the pathogenesis of CNE include tissue-culture based growth for propagation of intracellular pathogens and autoimmunohistochemistry on surgical specimens.…”
Section: Culture-negative Endocarditismentioning
confidence: 99%
“…Chronic Q fever generally presents as a culture-negative endocarditis or vascular infection with a high case fatality [3]. Another important long-term effect is Q fever fatigue syndrome, which occurs in 10 to 20% of all acute Q fever cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…The level of IgM increases rapidly after infection, thus is considered to be a marker of recent infection, however it can persist for many months [9], [10]. IgG levels increase a few weeks after infection, but remain detectable for years or even throughout life [5], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which C. burnetii is cleared from the blood is not known, but the timing correlates well with the development of immune responses (5). Although recent reports have suggested that C. burnetii DNA and antigen can be detected years after an acute infection, viable organisms are thought to be eliminated more quickly (6,7). However, the time required for complete clearance of viable C. burnetii in humans is not known.…”
mentioning
confidence: 99%